Pengaruh Pemberian Layanan Bimbingan Konseling Sekolah Terhadap Perilaku Disiplin Siswa - Helmyati Allorerung; Tritjahjo Danny Soesilo; Sapto Irawan (Peneliti.net, 2023)
This research was conducted at Christian Middle School 2 Salatiga grades VIII A and B with a total of 60 students and was the total sample. This study aims to determine the significance of the Influence of Providing School Counseling Services on the Discipline Behavior of Class VIII Students at Christian Middle School 2 Salatiga. The measuring tool used in this study is Disciplinary Behavior which is compiled based on Arikunto's theory (2013) and School Counseling Services which is compiled based on Prayitno's theory (2012). The analysis technique used is linear regression which is processed with the help of the SPSS version 26.0 for Windows program. There is a RSquare value: 0.280 indicating the coefficient of determination (R2). This means that the contribution of the BK Service variable to the Disciplinary Behavior variable is 28%, the rest (72%). The regression results obtained from the counseling services variable have a Sig value. 0.000, because sig. 0.000 <0.050, meaning that there is a significant effect of the School Counseling Service on the Disciplinary Behavior of Grade VIII Students at Christian Middle School 2 Salatiga